2019
DOI: 10.1080/24750263.2019.1572798
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of adipose tissue in Tupaia belangeri (Mammalia: Scandentia: Tupaiidae)

Abstract: Animals employ various strategies to adapt to different natural habitats. In order to investigate the relationship between thermogenesis of adipose tissue and seasonal variations in Tupaia belangeri, body mass, food intake, adipose tissue morphology, and expression levels of three adipose differentiation-related genesperoxisome proliferators-activated receptor α (PPARα), cyclooxygenase-2 (COX-2) and peroxisome proliferator-activated receptor γ coactivator 1-α (PGC-1α)were measured in the present study. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…WAT is the major energy reserve and will be mobilized to supply energy metabolism during increased physiological demand, such as prolonged cold acclimation. In addition, inguinal WAT will undergo browning, with increased UCP1 expression to produce heat uncoupling from ATP production, when animals are stimulated by cold [50]. Loss of classic iBAT in mice enhanced WAT browning [51], our research has similar results, which means iBAT removal induced browning of WAT.…”
Section: Effect Of Cold and Removal On Metabolic Phenotype Thermogene...supporting
confidence: 69%
“…WAT is the major energy reserve and will be mobilized to supply energy metabolism during increased physiological demand, such as prolonged cold acclimation. In addition, inguinal WAT will undergo browning, with increased UCP1 expression to produce heat uncoupling from ATP production, when animals are stimulated by cold [50]. Loss of classic iBAT in mice enhanced WAT browning [51], our research has similar results, which means iBAT removal induced browning of WAT.…”
Section: Effect Of Cold and Removal On Metabolic Phenotype Thermogene...supporting
confidence: 69%
“…The study about Tupaia belangeri shows that RMR and the expression levels of pparα , pgc-1α , and PRDM16 increase significantly under cold acclimation, suggesting that browning may appear in WAT ( Hou et al, 2020 ). A genomic, proteomic, and morphological study of energy metabolism in highland pikas and Tupaia belangeri in summer and winter studies revealed that subcutaneous WAT in winter show BAT morphological and histological features ( Li et al, 2019 ). Furthermore, BAT-specific genes, such as UCP1 , Cox4 , and pgc-1α , are highly expressed in WAT in winter ( Li J. et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that at different altitudes, the life history strategies and personalities of plateau pika varied significantly ( Liu et al, 2012 ; Qu et al, 2013 ; Qu et al, 2019 ; Tan et al, 2020 ), accompanied by differences in fat accumulation and metabolic rate ( Yang et al, 2006 ). As ambient temperatures decrease, subcutaneous WAT “browned”, and adipose tissue heat production increased ( Bai et al, 2015 ; Li et al, 2019 ). However, studies on the expression of thermogenic genes in adipose tissue and other thermogenic tissues of plateau pika at different altitudes are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, mammalian adipose tissue was classified as white and brown adipose tissues, but in recent years another adipose tissue called ‘beige’ was found, which differs from white adipose tissue (e.g., Li et al., 2019; Wang et al., 2014). White adipocytes have larger lipid drops and store energy in the form of triacylglycerols, secreting hormones and cytokines to regulate energy metabolism (Nedergaard et al., 2007); in contrast, brown adipocytes have smaller lipid drops and a greater number of mitochondria with UCP1, a mitochondrial carrier protein in their inner membrane, involved in the processes of generating heat.…”
Section: Discussionmentioning
confidence: 99%